The Role of the Homeroom Teacher in Improving Discipline of Family Dysfunction Students at Labschool STKIP Muhammadiyah High School, Sorong Regency, Southwest Papua - Khoiri, Abdul Azis (Riwayat: Educational Journal of History and Humanities, 2025)
Family dysfunction is a condition where there is conflict or disagreement between one individual and another individual in a family, causing a loss of affection, warmth and a sense of well-being. Respect each family member. This research aims to determine the forms of dysfunction family, description of student discipline, family dysfunction, and the role of guardians class in improving the discipline of family dysfunction students in high school Labschool STKIP Muhammadiyah Sorong Regency. This type of research is descriptive with a qualitative approach. The results of the research show that the dysfunction that occurs in students at SMA Labschool STKIP Muhammadiyah Sorong Regency, namely education, economics, and communication. An overview of student discipline This dysfunctional family experiences problems with school violations, including not doing assignments on time, not wearing uniforms according to the rules, skipping school, and speaking harshly towards teachers. The role of the homeroom teacher is in improving student discipline family dysfunction, namely, advice and guidance, motivational and enthusiastic support, direction obtained through interpersonal guidance, emotional approaches, exemplary discipline, routine supervision, and collaboration with the school, family and community.